Animal Choice Behavior. - Mazur, James (Fall ; Psychology., 1995)
Keywords: dept.psy; faculty_collection; sabbatical_report

Conditioned reinforcement and choice with delayed and uncertain primary reinforcers - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1995)
In an adjusting-delay choice procedure, pigeons could peck on either a red key or a green key. A peck on the red key always led to a delay associated with red houselights and then food. The delay was adjusted over trials to estimate an indifference point-a delay at which the two keys were chosen about equally often. In some conditions, a peck on the green key led to food on all trials after delays of either 10 a or 30 s, and green houselights were lit during the delays. In other conditions, food was presented on only half of the green-key trials. If the green houselights continued to occur on both reinforcement and nonreinforcement trials, preference for the green key always decreased. Preference for the green key also decreased if half of the trials had 30-s houselights followed by food and the other half had no green houselights and no food. However, preference for the green key actually increased if half of the trials had 10-s green houselights followed by food and the other half had no green houselights followed by no food. The latter condition therefore demonstrated a case in which preference for an alternative increased when food was removed from half of the trials. The results suggest that the red and green houselights served as conditioned reinforcers. A hyperbolic decay model (Mazur, 1989) provided good predictions for all conditions by assuming that the strength of a conditioned reinforcer is inversely related to the total time spent in its presence before food is delivered.
Keywords: Animal; Association Learning; Choice Behavior; Color Perception; Conditioning, Operant; Discrimination Learning; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Retention (Psychology); Support, U.S. Gov't, P.H.S.; animal; article; choice; color vision; conditioned reinforcement; decision making; delay of reinforcement; dept.psy; discrimination learning; instrumental conditioning; key peck; learning; long term memory; motivation; pigeon; pigeons; probability of reinforcement; recall; reinforcement

Development of preference and spontaneous recovery in choice behavior with concurrent variable-interval schedules - Mazur, James E (Animal Learning & Behavior, 1995)
Pigeons pecked on two response keys that delivered reinforcers on a variable-interval schedule. The proportion of reinforcers delivered by one key was constant for a few sessions and then changed, and subjects' choice responses were recorded during these periods of transition. In Experiment 1, response proportions approached a new asymptote slightly more slowly when the switch in reinforcement proportions was more extreme. In Experiment 2, slightly faster transitions were found with higher overall rates of reinforcement. The results from the first session, after a switch in the reinforcement proportions, were generally consistent with a mathematical model that assumes that the strength of each response is increased by reinforcement and decreased by nonreinforcement. However, neither this model nor other similar models; predicted the `'spontaneous recovery” observed in later sessions: At the start of these sessions, response proportions reverted toward their preswitch levels. Computer simulations could mimic the spontaneous recovery by assuming that subjects store separate representations of response strength for each session, which are averaged at the start of each new session.
Keywords: animal behavior; article; decision making; dept.psy; mathematical model; nonhuman; pigeon; reinforcement

Developmental differences in the symptomatology of psychiatric-inpatients with and without mild mental-retardation - Glick, M; Zigler, E (American Journal on Mental Retardation, 1995)
The symptomatology of psychiatric inpatients with mild mental retardation was compared with that of a matched sample of inpatients without mental retardation. An integration of the developmental position on mental retardation with the developmental approach to adult psychopathology generated the hypotheses that, compared to patients without mental retardation, patients with mild mental retardation would display (a) more symptoms indicative of turning against others and fewer symptoms indicative of turning against the self, (b) more symptoms involving expression in action rather than thought, and (c) psychotic symptom pictures that more frequently involve hallucinations without delusions and infrequently involve delusions alone. All hypotheses were confirmed.
Keywords: *Intellectual Disability/co [Complications]; *Mental Disorders/co [Complications]; Adult; Delusions/et [Etiology]; Female; Hallucinations/et [Etiology]; Hospitalization; Hospitals, Psychiatric; Humans; Male; Mental Disorders/px [Psychology]; Mental Disorders/rh [Rehabilitation]; dept.psy; ⛔ No DOI found